2007
DOI: 10.1128/aac.01249-06
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activity of Dispersin B and Cefamandole Nafate in Inhibition of Staphylococcal Biofilm Growth on Polyurethanes

Abstract: Antibiotic therapies to eradicate medical device-associated infections often fail because of the ability of sessile bacteria, encased in their exopolysaccharide matrix, to be more drug resistant than planktonic organisms. In the last two decades, several strategies to prevent microbial adhesion and biofilm formation on the surfaces of medical devices, based mainly on the use of antiadhesive, antiseptic, and antibiotic coatings on polymer surfaces, have been developed. More recent alternative approaches are bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
119
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(133 citation statements)
references
References 32 publications
2
119
1
3
Order By: Relevance
“…For example, dispersin B is a ␤-hexosaminidase produced by the Gram-negative bacterium Aggregatibacter actinomycetemcomitans in order to disperse adherent cells from a mature biofilm (12). It has been shown that exogenous addition of dispersin B is capable of preventing and disrupting biofilms in vitro and in vivo (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…For example, dispersin B is a ␤-hexosaminidase produced by the Gram-negative bacterium Aggregatibacter actinomycetemcomitans in order to disperse adherent cells from a mature biofilm (12). It has been shown that exogenous addition of dispersin B is capable of preventing and disrupting biofilms in vitro and in vivo (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Antibiotic coating of medical devices is a commonly deployed technique but has been found to be of limited value, due to a number of factors including poor penetration of the biofilm matrix, transfer of antibiotic resistance via plasmids, high incidence of poly microbial infections, and decreased metabolic state of biofilm bacteria decreasing antibiotic susceptibility [40]. Initial design of antibiotic impregnated medical devices (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Одним из существующих на сегодняшний день методов борьбы с бактериальными инфекциями, лишенных таких недостатков антибиотиков, как снижение концентрации агента с течением времени и возможные аллергические реакции, являются естественные вирусы, инфицирующие бактерии -бактериофаги [6]. В силу особенностей строения и активности бактериофаги способны преодолевать экзополимерный субстрат биопленок, вызывая значительные изменения в самих биопленках [13] и уничтожать бактерии внутри биопленки, что в случае антибиотиков возможно далеко не для каждого антибиотика.…”
Section: рис 1 электронная микроскопия образцов биоматериала а -биunclassified